2011
DOI: 10.1523/jneurosci.3967-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Authentically Phosphorylated α-Synuclein at Ser129 Accelerates Neurodegeneration in a Rat Model of Familial Parkinson's Disease

Abstract: Parkinson's disease (PD) is characterized by the loss of dopaminergic neurons in the substantia nigra (SN) and the appearance of fibrillar aggregates of insoluble ␣-synuclein (␣-syn) called Lewy bodies (LBs). Approximately 90% of ␣-syn deposited in LBs is phosphorylated at serine 129 (Ser129). In contrast, only 4% of total ␣-syn is phosphorylated in normal brain, suggesting that accumulation of Ser129-phosphorylated ␣-syn is involved in the pathogenesis of PD. However, the role of Ser129 phosphorylation in ␣-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 44 publications
4
103
2
2
Order By: Relevance
“…However, the relevance of αS phosphorylation at S129 for neurotoxicity and disease remains controversial (Basso et al, 2013). While some reports report a beneficial effect (Kuwahara et al, 2012;Oueslati et al, 2013), others identified deleterious consequences (Chen and Feany, 2005;Sato et al, 2011). A separate study found no effects of this posttranslational modification (McFarland et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of αS phosphorylation at S129 for neurotoxicity and disease remains controversial (Basso et al, 2013). While some reports report a beneficial effect (Kuwahara et al, 2012;Oueslati et al, 2013), others identified deleterious consequences (Chen and Feany, 2005;Sato et al, 2011). A separate study found no effects of this posttranslational modification (McFarland et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic Drosophila, the coexpression of α-syn with GRK2 enhances α-syn phosphorylation at S129 and accelerates neuronal loss compared with nonphosphorylated α-syn (45). Recently, Sato et al reported that GRK6 overexpression moderately accelerates A53T α-syn toxicity in an AAV-based rat model of PD, in an α-syn phosphorylation-dependent manner (46). Therefore, clear discrepancies are found between different kinases with respect to their effect on α-syn toxicity in vivo.…”
Section: Plk2 Activity Enhances α-Syn Autophagic Clearance In Cell Cumentioning
confidence: 99%
“…Perhaps modulating the activity of the G protein-coupled receptor kinase (GRK) 2, another kinase known to phosphorylate α-synuclein at Ser129 [188,191,210], or AMP kinase, whose overexpression increases aggregation and causes decreased neurite outgrowth in primary neuronal cultures [211], may be beneficial. Interestingly, α-synuclein phosphorylation [212] and pathogenicity may be mediated, at least in part, by LRRK2 [213], a kinase that when mutated causes inherited forms of PD and which is the target of extensive drug discovery efforts.…”
Section: Phosphorylationmentioning
confidence: 99%